Implementasi Pembentukan Karakter pada Siswa SD Islam Terpadu - Muhammad Rangga Gumilar (Jurnal Dirosah Islamiyah, 2023)
This study aims to describe the implementation of character building in learning and to find out several factors supporting and inhibiting the application of character building in learning in Integrated Islamic Elementary Schools (SDIT). This study uses a qualitative method. Data collection was carried out through interviews and observation, documentation, and descriptive and qualitative data analysis. The results of this study indicate that the implementation of character building in schools is integrated into all subjects, extracurricular activities, and habituation activities for each student. The results of this study are expected to be useful for educators and education staff to improve the quality of learning related to the formation of student character. Keywords: Islamic elementary school, character building, learning.